Two necessary (and doable) amendments to Law No. 40/2004: Withdrawal of consent and access to assisted reproduction for single women - Zaami, Simona; Montanari Vergallo, Gianluca; Circosta, Francesco; Krysiak, Robert (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: It has been twenty years since the Italian legislator enacted Law No. 40/2004 on medically assisted procreation (MAP). This is a highly ideologized law, which the Constitutional Court has largely modified over the years. The new guidelines issued by the Ministry have incorporated the Court's decisions; however, they have overlooked certain issues that can only be regulated by the legislator: namely, the consent to embryo implantation and the possibility for single women to access assisted reproduction techniques. As has already occurred with end-of-life issues, the legislator has not yet enacted any set of norm aimed at taking into account the demands coming from society and protects the rights of all individuals involved in assisted procreation techniques. In fact, the political direction has gone in the opposite way, even classifying surrogacy as a "universal crime." (www.actabiomedica.it)